Analysis of Service Quality in Improving Patient Satisfaction and Loyalty in Pratama Berkah Sehat - Helena Nurhayati; Siti Dyah Handayani; Firman Pribadi (Postgraduate, University of Mataram, 2024)
Health services cannot be separated from the demands of competition in all aspects. Good service management is needed to create the health services the surrounding community needs so that the community feels satisfaction with health services as one of the businesses that must be carried out. The research design used in this research is quantitative. The population and sample used for this study were all patients who were treated at the Berkah Sehat Primary Clinic, totaling 200 patients. All of the 200 patients who sought treatment at the Berkah Sehat Pratama Clinic between March 2023 and April 2023 comprised the population and sample for this study. The study's objective was to examine the impact of the clinic's doctor, pharmaceutical, laboratory, and patient loyalty quality levels. Data analysis used Structural Equation Modeling (SEM) analysis with the Amos application version 24, Excel, and Spss. With a factor loading value of 0.989, assurance receives the best ranking for doctor services. With a factor loading value of 0.957, assurance receives the best grade in the pharmaceutical services category. With a factor loading value of 0.982, reliability receives the highest ranking for laboratory technician services. Product quality has the greatest factor loading value for patient satisfaction, at 0.965. The statement that I won't visit any clinic because I am satisfied with the services offered at the Berkah Sehat Primary Clinic with a loading factor value of 0.798 and the statement that if one day my family or friends need medical care, I would advise them to visit the Berkah Sehat Pratama Clinic with a loading factor value of 0.798 represent the highest assessments of patient loyalty. The results of the direct impact analysis show that doctors service quality, pharmacy service quality, and laboratory technician service quality influence patient loyalty. Patient satisfaction can influence the impact of the quality of service of doctors, pharmaceutical companies and laboratory technicians on loyalty at Berkah Sehat Primary Clinic.